THE URGENCY OF THE FARMER CARD POLICY IN IMPROVING THE WELFARE OF FARMERS IN INDONESIA - Abdul Nadjib; Deni Gunawan; Etty Sri Hertini; Nanda Dwi Rizkia; Sintya Purwandaningsih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to (1) describe the scheme for distributing farmer cards to farmers; and (2) describe the urgency of implementing the farmer Card policy in improving the welfare of farmers in Indonesia. This research is qualitative-descriptive research. The results of this research show that (1) the scheme for distributing farmer cards to farmers is carried out through two models, namely non-cash fertilizer assistance funds and subsidized fertilizer quotas; (2) the urgency of implementing the Farmer's Card policy in improving the welfare of farmers in Indonesia, including equalizing agricultural fertilizer prices nationally, subsidized fertilizer policies that can be controlled by the government, and the effectiveness of the farmer's card policy in line with farmers' knowledge regarding the policy.